Indirect Costs of Myocardial Infarction in Portugal - Timóteo, AT (2021)
Introduction: Cardiovascular disease, and particularly myocardial infarction (MI), carries a significant economic burden, through productivity losses (indirect costs) associated with temporary absence from work, that has not yet been adequately studied in Portugal. Our objective was to quantify the indirect costs of MI in the first year after admission. Methods: Consecutive patients admitted to a single center aged <66 years who survived to discharge during a one-year period were included. Employment status on admission was assessed and for every employed patient, their monthly wage was estimated from market wage rates taken from the Ministry of Labor database according to gender and age. The duration of temporary absence from work was assessed in follow-up contacts for up to one year. Indirect costs were calculated in this sample and the results were applied to the number of MIs in Portugal during 2016 and separately to ST-elevation MI (STEMI) and non-ST-elevation acute coronary syndrome. Results: A total of 219 patients were included, of whom 66.2% were working. The mean monthly labor cost was 1802 euros. A total cost of 760 521.55 euros was obtained. At national level there were 4133 patients aged <66 years admitted with acute MI who survived to discharge. Costs were higher in STEMI patients and the total indirect cost was estimated at 10.12 million euros. Conclusions: In Portugal, the costs to society of disability-generated productivity losses exceed ten million euros in the first year after MI. Strategies to promote an earlier return to work are needed to lower these costs.